Retrospective Study of Acute Pediatric Intoxication Cases by Household Products Presented to the Poison Control Center of Ain-Shams University Hospitals - Sherien Salah Ghaleb1 , Lamiaa Ewis Abd Alfatah2 , Hoda Sayed Mahmoud3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Acute poisoning in children is a crucial pediatric emergency and may be a worldwide problem.This study aims to acknowledge the incidence of acute poisoning by household products in children regardingdemographic factors, common clinical presentation and outcome of management.Methods: this is often a descriptive retrospective study conducted on patients admitted to the Poison ControlCentre of Ain-Shams University Hospital. The duration of the study was one year, from the beginning ofJanuary, 2016 till the top of December, 2016. the entire number of cases was 846 cases collected and analyzedregarding the demographic data, condition of poisoning, common clinical presentation, and managementplan. Data was analyzed using computer software package SPSS 15.Results: a complete of 846 cases were reviewed, the varied age groups involved ranged from but one year to18 years, with a mean age of 10.22 ± 6.83 years. Most cases were females (67 %), living in urban areas (52.4%) and therefore the majority of cases were accidental (74 %). the foremost common offending agent waspesticides (71%). Most of the patients were vitally stable on admission and therefore the commonest clinicalpresentation was gastrointestinal symptoms (31.3%). Most of cases received medical treatment within theinpatient wards (80.5%) and (96.7%) improved while (3.3 %) died.Conclusions: Acute poisoning by household products is common among adolescents and pre-school agechildren. Pesticides were liable for the bulk of cases. Supportive and symptomatic therapy is that the mainmethod for treatment.